2007
DOI: 10.1007/s00300-007-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Soft bottom species richness and diversity as a function of depth and iceberg scour in Arctic glacial Kongsfjorden (Svalbard)

Abstract: Macrozoobenthic soft-sediment communities of central Arctic Kongsfjorden inhabiting six depth zones between 5 and 30 m were sampled using SCUBA-diving during June-August 2003 and analysed comparatively. About 63 taxa were found, nine of which had not been reported for Kongsfjorden and four for Svalbard. Suspension feeding or surface and sub-surface detritivorous polychaetes and deposit-feeding amphipods were dominant. Only 11 of the 63 taxa (45 species and additional 18 families not further identiWed) inhabite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
1
30
2
Order By: Relevance
“…Iceberg scouring is likely to be one of the most common disturbances in those benthic habitats. In fact, Laudien et al (2007) related macrobenthic community differences of the same habitat to scouring. The only existing study recording shallow water meiofauna recovery after iceberg impact stems from the Antarctic (Lee et al, 2001).…”
Section: Colonisation and Community Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Iceberg scouring is likely to be one of the most common disturbances in those benthic habitats. In fact, Laudien et al (2007) related macrobenthic community differences of the same habitat to scouring. The only existing study recording shallow water meiofauna recovery after iceberg impact stems from the Antarctic (Lee et al, 2001).…”
Section: Colonisation and Community Developmentmentioning
confidence: 99%
“…Physical disturbances both on spatial and temporal scales are thus highly variable. Laudien et al (2007) assume that for macrobenthic infaunal communities at Kongsfjorden iceberg scouring may be the main structuring force, capable of producing up to 5 m deep plough marks (pers. observ.…”
Section: Introductionmentioning
confidence: 99%
“…The average tidal amplitude in Kongsfjorden is 1.8 m (Svendsen et al 2002). The soft-bottom community of the study site is dominated by polychaetes, molluscs and crustaceans (Laudien et al 2007). Stones (B 0.3 m in diameter) covered mainly with kelp (primarily Saccharina latissima (L.) C.E.Lane, C.Mayes, Druehl and G.W.Saunders, but also with Alaria esculenta (L.) Greville and Desmarestia sp.)…”
Section: Study Sitementioning
confidence: 98%
“…To avoid edge effects, each sample was taken at a minimum distance of 10 cm from plot margins by pushing a sediment corer of 5.2 cm diameter five centimetres deep into the sediment. This method (adopted from Petrowski et al 2015) was shown to generate representative samples of the soft-bottom fauna at the study site and produced a comparable taxon list to that compiled by Laudien et al (2007) who used larger corers (20 cm ø) that were pushed deeper (20 cm) into the sediment than in this study. Samples were transported within 2 h to the Marine Laboratory in Ny-Å lesund and stored in a cooler at 5°C.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation